Factors Associated With The Incidence Of Hypertension In Patients With Type 2 Diabetes Mellitus At The Central Cigugur Health Center - Ayu Lestari, Vika (Jurnal Kesehatan Siliwangi, 2024)
Individuals with type 2 diabetes mellitus have elevated blood glucose levels (hyperglycemia). This results in an increase in body fluid volume and damages the vascular system and will cause peripheral arterial resistance to increase which ultimately causes hypertension. The prevalence of type 2 diabetes mellitus and hypertension in the Cigugur Tengah Health Center area is still increasing every year. The purpose of this study was to determine the factors associated with the incidence of hypertension in patients with type 2 diabetes mellitus at the Cigugur Tengah Health Center. This type of research is descriptive analytic research with a cross sectional research design. The population and sample of this study were type 2 diabetes mellitus patients with a doctor's diagnosis who were willing to become respondents and were registered in the Central Cigugur Health Center area, totaling 59 people. Sampling was carried out using the total population technique where the sample was treated the same as the population and using a questionnaire sheet. Data analysis using the Chi-Square Test using the SPSS program. The results showed that there was a significant relationship between the age factor with a value of P= 0.023 <0.05, the gender factor with a value of P= 0.037 <0.05, the drug consumption compliance factor with a value of P= 0.010 <0.05, the length of suffering with a value of P= 0.043 <0.05, and there was no relationship between the Body Mass Index factor with a value of P= 0.289>0.05 with the incidence of the disease.